The Naked bear: folktales of the Iroquois - Zimmer, Dirk.; Bierhorst, John. (Morrow, 1987)
A collection of sixteen traditional tales told by the Iroquois Indians, some featuring talking animals and some presenting terrifying flesh-eating creatures such as the Naked Bear, the Stone Coat, and the Whirlwinds.
Bibliography: p. 121-123
A collection of sixteen traditional tales told by the Iroquois Indians, some featuring talking animals and some presenting terrifying flesh-eating creatures such as the Naked Bear, the Stone Coat, and the Whirlwinds.
Keywords: Indians of North America / Legends.; Iroquois Indians / Legends.; Indians of North America / Folklore.; Iroquois Indians / Folklore.